In vivo Ca2+ dynamics induced by Ca2+ injection in individual rat skeletal muscle fibers - Wakizaka, M.; Eshima, H.; Tanaka, Y.; Shirakawa, H.; Poole, David C.; Kano, Y. (My University, 2017)
In contrast to cardiomyocytes, store overload-induced calcium ion (Ca2+) release (SOICR) is not considered to constitute a primary Ca2+ releasing system from the sarcoplasmic reticulum (SR) in skeletal muscle myocytes. In the latter, voltage-induced Ca2+ release (VICR) is regarded as the dominant mechanism facilitating contractions. Any role of the SOICR in the regulation of cytoplasmic Ca2+ concentration ([Ca2+](i)) and its dynamics in skeletal muscle in vivo remains poorly understood. By means of in vivo single fiber Ca2+ microinjections combined with bioimaging techniques, we tested the hypothesis that the [Ca2+](i) dynamics following Ca2+ injection would be amplified and fiber contraction facilitated by SOICR. The circulation-intact spinotrapezius muscle of adult male Wistar rats (n = 34) was exteriorized and loaded with Fura-2 AM to monitor [Ca2+](i) dynamics. Groups of rats underwent the following treatments: (1) 0.02, 0.2, and 2.0 mmol/L Ca2+ injections, (2) 2.0 mmol/L Ca2+ with inhibition of ryanodine receptors (RyR) by dantrolene sodium (DAN), and (3) 2.0 mmol/L Ca2+ with inhibition of SR Ca2+ ATPase (SERCA) by cyclopiazonic acid (CPA). A quantity of 0.02 mmol/L Ca2+ injection yielded no detectable response, whereas peak evoked [Ca2+](i) increased 9.9 +/- 1.8% above baseline for 0.2 mmol/L and 23.8 c 4.3% (P < 0.05) for 2.0 mmol/L Ca2+ injections. The peak [Ca2+](i) in response to 2.0 mmol/L Ca2+ injection was largely abolished by DAN and CPA (-85.8%, -71.0%, respectively, both P < 0.05 vs. unblocked) supporting dependence of the [Ca2+](i) dynamics on Ca2+ released by SOICR rather than injected Ca2+ itself. Thus, this investigation demonstrates the presence of a robust SR-evoked SOICR operant in skeletal muscle in vivo.
Citation: Wakizaka, M., Eshima, H., Tanaka, Y., Shirakawa, H., Poole, D. C., & Kano, Y. (2017). In vivo Ca2+ dynamics induced by Ca2+ injection in individual rat skeletal muscle fibers. Physiological Reports, 5(5), 10. doi:10.14814/phy2.13180
Keywords: Ca2+-Induc Ca2+ Release; Ryanodine Receptor; Sarcoplasmic Reticulum; Store Overload-Induced Ca2+ Release; Ca-2+ Release Channel; Sarcoplasmic-Reticulum